2019
DOI: 10.1182/bloodadvances.2019000050
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of haploidentical vs matched sibling transplantation for acute myeloid leukemia in first complete remission

Abstract: HLA-haploidentical hematopoietic cell transplantation (Haplo-HCT) using posttransplantation cyclophosphamide (PT-Cy) has improved donor availability. However, a matched sibling donor (MSD) is still considered the optimal donor. Using the Center for International Blood and Marrow Transplant Research database, we compared outcomes after Haplo-HCT vs MSD in patients with acute myeloid leukemia (AML) in first complete remission (CR1). Data from 1205 adult CR1 AML patients (2008-2015) were analyzed. A total of 336 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 31 publications
3
72
0
Order By: Relevance
“…In a CIBMTR retrospective study in patients who underwent transplantation for AML in CR1, 336 who underwent a PTCY‐based HAPLO transplantation were compared with 869 who underwent an MSD transplantation using calcineurin GVHD prevention. The HAPLO group had a significantly lower incidence of cGVHD but had similar other outcomes, leading to the conclusion that a HAPLO transplantation with PTCY was a viable alternative to MSD transplantation in this patient population . Finally, in a recent joint EBMT‐CIBMTR study, patient age appeared to be important, with equivalent outcomes reported using MSDs or HAPLO donors in patients aged <55 years, but with better outcomes using MSDs in older patients …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a CIBMTR retrospective study in patients who underwent transplantation for AML in CR1, 336 who underwent a PTCY‐based HAPLO transplantation were compared with 869 who underwent an MSD transplantation using calcineurin GVHD prevention. The HAPLO group had a significantly lower incidence of cGVHD but had similar other outcomes, leading to the conclusion that a HAPLO transplantation with PTCY was a viable alternative to MSD transplantation in this patient population . Finally, in a recent joint EBMT‐CIBMTR study, patient age appeared to be important, with equivalent outcomes reported using MSDs or HAPLO donors in patients aged <55 years, but with better outcomes using MSDs in older patients …”
Section: Discussionmentioning
confidence: 94%
“…The HAPLO group had a significantly lower incidence of cGVHD but had similar other outcomes, leading to the conclusion that a HAPLO transplantation with PTCY was a viable alternative to MSD transplantation in this patient population. 4 Finally, in a recent joint EBMT-CIBMTR study, patient age appeared to be important, with equivalent outcomes reported using MSDs or HAPLO donors in patients aged <55 years, but with better outcomes using MSDs in older patients. 46 In view of these results, we considered a practical possible clinical issue: ie, what would be the best choice for transplantation in a male patient with intermediate-risk or high-risk AML who has a unique genoidentical sister available.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In both cases, the risk of GVHD (especially chronic GVHD) is surprising low. Although the reasons for this are incompletely understood, several factors, such as the intensity of the immunosuppression in haplo-identical AHCT, or the intrinsic features of the graft in terms of cell composition and functionality in cord blood transplants, may contribute to this observation (29,30). Moreover, in certain circumstances, the risk of relapse appears to be lower following these mismatched transplants, arguing in favor of enhanced GVT in these settings (31)(32)(33).…”
Section: Target Antigens In Hematological Cancers Histocompatibility mentioning
confidence: 99%
“…Nonetheless, the timely availability of a matched unrelated donor (MUD), high incidences of chronic GvHD (cGvHD), and high relapse rates remain well-known obstacles to the overall improvement of outcome after allogeneic HSCT [2,3]. As most patients have multiple potential haploidentical family donors, recent advances in both T-cell-replete and T-celldepleted haploidentical HSCT have overcome donor shortage and are now challenging the standard use of matched HSCT without compromising outcomes [4][5][6][7][8][9][10][11][12][13][14]. In vivo depletion of alloreactive T cells with posttransplant cyclophosphamide (PTCY) is the most frequently utilized approach to haploidentical HSCT, yet severe GvHD still occurs despite use of immunosuppression and relapse remains an ongoing concern [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%